APPLICATION ANALYTICAL INFORMATION SYSTEMS BASED ON OLAP TECHNOLOGY - L. Dumanskaya; S. Dumansky (Вестник университета)
Тhis article describes a prototype of Information Analytical system (IAS) based on OLAP model for the diagnosis of diseases. It has been shown the structural elements of the IAS and OLAP model. The algorithm elaborated can recognize painful human condition, depending on the set of detectible symptoms and syndromes. This prototype IAS can be used of to explore different domains of human activity, which can be applied to problems related to pattern recognition class.